2013
DOI: 10.1093/cid/cit070
|View full text |Cite
|
Sign up to set email alerts
|

Seven Ways to Preserve the Miracle of Antibiotics

Abstract: Antibiotic resistance is a well-acknowledged crisis with no clearly defined comprehensive, national corrective plan. We propose a number of interventions that, collectively, could make a large difference. These include collection of data to inform decisions, efforts to reduce antibiotic abuse in people and animals, great emphasis on antibiotic stewardship, performance incentives, optimal use of newer diagnostics, better support for clinical and basic resistance-related research, and novel methods to foster new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
311
0
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(334 citation statements)
references
References 33 publications
5
311
0
18
Order By: Relevance
“…In support of the choice of this intervention, several studies have shown that a shorter duration of antibiotic treatment is equivalent to the traditional longer durations. 13 We made the decision to restrict the number of concurrently administered antimicrobials mainly because previous treatments are not necessarily discontinued on initiation of a new antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the choice of this intervention, several studies have shown that a shorter duration of antibiotic treatment is equivalent to the traditional longer durations. 13 We made the decision to restrict the number of concurrently administered antimicrobials mainly because previous treatments are not necessarily discontinued on initiation of a new antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of microfuidics for the filtering of blood may be infeasible due to he large blood volumes and flow rates required for processing, relative to the volumes and flow rates ammenable to microfluidic processing. While NP targeting has been long appreciated, and has been employed in high-priced cancer treatments, the translation of NP-antibiotic constructs has been hindered due to the high cost of most NP formation processes relative to the low price of antibiotic therapies (Bartlett et al 2013;Piddock 2012). In addition, the use of microfluidics for the filtering of blood may be unfeasible due to the large blood volumes and flow rates required for processing, relative to the volumes and flow rates permitted in microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Some pollutants groups have received special attention since the late 90s [4], due to correlations between the development and rapid expansion of antibiotic resistance and their total consumption and occurrence in the environment [4,5]. According to Bartlett et al [88], the resistance within all microbial classes continues to grow by a natural evolution driven by the massive use of agents that apply selective antimicrobial pressure, and pharmaceutical development that had previously kept men ahead of resistance is now stalled due to economic and regulatory barriers.…”
Section: Removal Of Pharmaceuticals By Fe 3 O 4 @C Core-shell Nanoparmentioning
confidence: 99%